2012
DOI: 10.1016/j.jjcc.2012.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of systolic blood pressure at admission on in-hospital outcome after primary percutaneous coronary intervention for acute myocardial infarction

Abstract: These results suggest that admission SBP 141-158 mmHg might be correlated with better in-hospital prognosis, whereas admission SBP<105 mmHg was associated with in-hospital death in Japanese AMI patients undergoing primary PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 20 publications
3
19
2
Order By: Relevance
“…We have already shown that admission SBP or PP in a certain interval between an extremely low subset and extremely high subset might be associated with a lower in-hospital mortality in Japanese AMI patients undergoing primary percutaneous coronary intervention (PCI), which followed a J-or U-shaped curve pattern. 8,9) However, sufficient data regarding the effects of the steady component of blood pressure, MBP, at admission on the prognosis in AMI patients are still lacking. 10) The AMI-Kyoto Multi-Center Risk Study, a large multicenter observational study in which collaborating hospitals in Kyoto Prefecture have collected demographic, procedural, and outcome data on AMI patients, was established in 2000 in order to analyze this data and establish an emergency-hospital network for heart diseases in Kyoto.…”
Section: B Ased On Numerous Reports From Western Countries Anmentioning
confidence: 99%
See 1 more Smart Citation
“…We have already shown that admission SBP or PP in a certain interval between an extremely low subset and extremely high subset might be associated with a lower in-hospital mortality in Japanese AMI patients undergoing primary percutaneous coronary intervention (PCI), which followed a J-or U-shaped curve pattern. 8,9) However, sufficient data regarding the effects of the steady component of blood pressure, MBP, at admission on the prognosis in AMI patients are still lacking. 10) The AMI-Kyoto Multi-Center Risk Study, a large multicenter observational study in which collaborating hospitals in Kyoto Prefecture have collected demographic, procedural, and outcome data on AMI patients, was established in 2000 in order to analyze this data and establish an emergency-hospital network for heart diseases in Kyoto.…”
Section: B Ased On Numerous Reports From Western Countries Anmentioning
confidence: 99%
“…We have already shown that admission SBP or PP in a certain interval between an extremely low subset and extremely high subset might be associated with a lower in-hospital mortality in Japanese AMI patients undergoing primary percutaneous coronary intervention (PCI), which followed a J-or U-shaped curve pattern. 8,9) However, sufficient data regarding the effects of the steady component of blood pressure, MBP, at admission on the prognosis in AMI patients are still lacking. …”
mentioning
confidence: 99%
“…However, a limited number of studies have evaluated the prognostic value of elevated admission SBP and have reported conflicting results. Some studies6 7 reported that the admission SBP was inversely associated with the outcome; while others8 9 reported admission SBP in a certain interval with optimal outcome.…”
Section: Introductionmentioning
confidence: 99%
“…10) network for heart diseases in Kyoto. 11) The purpose of the present study was therefore to examine the prognostic impact of admission CKD and admission anemia on PCI results and in-hospital outcomes in Japanese AMI patients undergoing primary PCI, using data from the AMI-Kyoto Multi-Center Risk Study.…”
mentioning
confidence: 99%